Nutritional Status Deterioration Occurs Frequently During Children's ICU Stay*. Issue 8 (August 2019) - Valla, Frédéric V.; Baudin, Florent; Gaillard Le Roux, Bénédicte; Ford-Chessel, Carole; Gervet, Elodie; Giraud, Céline; Ginhoux, Tiphanie; Cour-Andlauer, Fleur; Javouhey, Etienne; Tume, Lyvonne
Abstract : Objectives: Malnutrition and faltering growth at PICU admission have been related to suboptimal outcomes. However, little is known about nutritional status deterioration during PICU stay, as critical illness is characterized by a profound and complex metabolism shift, which affects energy requirements and protein turnover. We aim to describe faltering growth occurrence during PICU stay. Design: Single-center prospective observational study. Setting: Twenty-three-bed general PICU, Lyon, France. Patients: All critically ill children 0–18 years old with length of stay longer than 5 days were included (September 2013–December 2015). Interventions: Weight and height/length were measured at admission, and weight was monitored during PICU stay, in order to calculate body mass index for age z score. Faltering growth was defined as body mass index z score decline over PICU stay. Children admitted during the first year of the study and who presented with faltering growth were followed after PICU discharge for 3 months. Measurements and Main Results: We analyzed 579 admissions. Of them, 10.2% presented a body mass index z score decline greater than 1 SD and 27.8% greater than 0.5. Admission severity risk scores and prolonged PICU stay accounted for 4% of the variability in nutritional status deterioration. Follow-up of post-PICU discharge nutritional status showed recovery within 3 months in most patients. Conclusions: Nutritional deterioration is frequent and often intense in critically ill children with length of stay greater than 5 days. Future research should focus on how targeted nutritional therapies can minimize PICU faltering growth and improve post-PICU rehabilitation. Abstract : Supplemental Digital Content is available in the text.